1985
DOI: 10.1007/bf01992773
|View full text |Cite
|
Sign up to set email alerts
|

Notes on growth and behaviour of the American razor clamEnsis directus in the Wadden Sea and the predation on it by birds

Abstract: Ensis directus (Conrad), a bivalve found in Europe only in the past few years, has filled an empty niche and spread rapidly over the intertidal fiats in the Wadden Sea. The growth of the animals was investigated using a few samples taken near Langeness in February 1984. The age of the animals could be determined by reading the clearly visible year marks on the shells. Notwithstanding the low density of E. directus, some oystercatchers appear to have already specialized in feeding on this new food source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
2

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 8 publications
1
25
0
2
Order By: Relevance
“…Dörjes (1992) assumed a maximum length up to 100 mm (2 years) for the Vogelsand. Mühlenhardt-Siegel et al (1983), Swennen et al (1985) and Palmer (2004) found also different maximum lengths at different study sites (Table 3). However, at both study sites, most individuals did not reach the maximum size.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Dörjes (1992) assumed a maximum length up to 100 mm (2 years) for the Vogelsand. Mühlenhardt-Siegel et al (1983), Swennen et al (1985) and Palmer (2004) found also different maximum lengths at different study sites (Table 3). However, at both study sites, most individuals did not reach the maximum size.…”
Section: Discussionmentioning
confidence: 74%
“…However, at both study sites, most individuals did not reach the maximum size. Optimal growth for the European E. directus is assumed generally in the deeper eulittoral respectively shallow sublittoral between 0 and 20 m depth (Swennen et al 1985;Beukema and Dekker 1995;Armonies and Reise 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Razor clams were accidently introduced to the Wadden Sea with ballast water in 1978 (Dannheim & Rumohr, 2012; Freudendahl, Nielsen, Jensen, & Jensen, 2010; von Cosel, Dörjes, & Mühlenhardt‐Siegel, 1982), and the species has since extended its range substantially over the last three decades (Dekker & Beukema, 2012). Common eiders, common scoters, and various shorebird and gull species regularly use this new source of food (Swennen, Leopold, & Stock, 1985; Tulp et al, 2010). Compared with other bivalve species, razor clams represent an energy‐rich prey organism with a good shell–flesh‐ratio (own unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…In the Wadden Sea, oystercatchers have been observed foraging on E. americanus at low tide (Swennen et al 1985;Dernedde 1994). Faecal and stomach studies of Common Eider from Norway and from the Danish and Dutch Wadden Sea have revealed E. americanus in its diet (Leopold 2002;Freudendahl and Nielsen 2003;Cadee 2006).…”
Section: Mortalitymentioning
confidence: 99%
“…They reach a refuge given the size-dependent burrow depth and their fast withdrawal response when approached by an enemy. Oystercatcher (Haematopus ostralegus) (Swennen et al 1985), gulls (Larus sp.) (Schneider 1982;Dernedde 1994;Knudsen 2001), Common Eider (Somateria mollissima) (Freudendahl and Nielsen 2003) and Common Scoter (Melanitta nigra) (B. Jacobsen, personal communication) are known as consumers of E. americanus, but to what extent their consumption inXuence the standing stock of clams is unknown.…”
Section: Introductionmentioning
confidence: 99%